Relationship Knowledge, Nutrition Status, Dietery, Food Taboo With Breast Milk Production of Breastfeeding Mother - Saskiyanto Manggabarani; Anto Jamma Hadi; Irfan Said; Selfi Bunga (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2018)
Breast milk is very important for a mother and her baby. The smooth production of breast milk given to the baby can have a positive impact on the baby's nutritional status. Objective; factors related to the smooth production of breast milk in breastfeeding mothers. This activity was held at Puskesmas Maradekaya Makassar City 2016. Materials and Methods; The type of research used was observational with Cross Sectional Study approach. The sample of this research is breastfeeding mother with purposive sampling sampling with amount of 97 breastfeeding mothers. Results; nutrition knowledge related with mothers breast milk production with p value (0.003), mother nutritional status is related with mothers breast milk production with p value (0,024), diet associated with mothers breast milk production with p value (0.013), food taboo related with mothers breast milk production with p value (0.001). Conclusion; knowledge of breast milk and nutrition, mother nutritional status, diet and food taboo related to the production of breast milk in breastfeeding mothers. It is expected that mothers increase knowledge about breastfeeding and nutrition in an active way, information provided through printed media (pamphlet) and listening from electronic media.